Vulnerability of port of Singapore as a maritime hub due to the impact of regional cooperation and partnership - Yang, Alvin Wei (2019)
With an increasingly connected world economy. Crisis in one part of the world can create ripples of instability to faraway nations and countries will no longer be fully protected from events far from their shore. Despite the uncertainty arising from the economic policy risks and the confluence of geopolitical. Growing intra-Asian trade provides an opportunity for the growth of regional cooperation and partnership between countries and even companies. Singapore’s position as a maritime hub may be affected in view of these developments as it changes the global shipping patterns. This paper aims to develop a quality function deployment approach to assess the vulnerability of the maritime hub due to the regional developments. Furthermore, recommendations will also be gathered to ensure the sustainability of the maritime hub. Both qualitative and quantitative field research was done to support and fulfil the objectives of this report.The research process consists of two parts. The first part includes the need for industry players to be surveyed extensively to generate scores by ranking the list of requirements of a maritime hub and the correlation between the requirements and the developments. The second part would be to conduct interviews with both the industry and academic experts to gather insights and recommendations on the research topic. Result shows that the top three developments are (1) Shipping Cooperation (2) Free Trade Agreements and (3) ASEAN Economic Community. In the short term, all these developments would not cause a significant impact due to the lack of financial capabilities in developing countries and counter measures taken proactively by Singapore’s maritime hub. However, in the long term, these developments could have an impact on Singapore’s maritime hub if proactive measures were not taken progressively. Two common themes were echoed among the interviewees where investing in technology and developing local talent pool will be required to ensure the sustainability of the maritime hub.